Arabinogalactan-proteins and the research challenges for these enigmatic plant cell surface proteoglycans - Tan, Li; Showalter, Allan M.; Egelund, Jack; Hernandez-Sanchez, Arianna; Doblin, Monika S.; Bacic, Antony (Frontiers in Plant Science, 2012)
Arabinogalactan-proteins (AGPs) are complex glycoconjugates that are commonly found at the cell surface and in secretions of plants. Their location and diversity of structures have made them attractive targets as modulators of plant development but definitive proof of their direct role(s) in biological processes remains elusive. Here we overview the current state of knowledge on AGPs, identify key challenges impeding progress in the field and propose approaches using modern bioinformatic, (bio)chemical, cell biological, molecular and genetic techniques that could be applied to redress these gaps in our knowledge.